Behind the Scenes of Independent Media: Production Dynamics and Regulatory Challenges in The Malaka Project - I Kadek Candika Wira Angga; Hafiz Bimo Nugroho; Bayu Wira Handyan; Deo Agung Sembada; Muhamad Nur Khotib (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2026)
Indonesia’s digital media ecosystem has rapidly transformed, creating space for independent outlets to emerge with alternative content and business models. Yet, little research has examined how such media sustain themselves amid structural pressures of capital and regulation. This study addresses that gap by analyzing the business model of The Malaka Project, a media collective recognized for its critical, value-based content. The purpose is to explore how The Malaka Project balances editorial independence, financial sustainability, and regulatory adaptation. This study applied a qualitative approach with in-depth interviews involving four key organizational members, namely a producer, editor, social media strategist, and finance officer, complemented by a literature review on media economy and business models. Data were thematically analyzed to identify patterns in content production, monetization, audience relations, and regulatory challenges. Results show that The Malaka Project strategically targets progressive youth, positioning itself as an educational platform rooted in Tan Malaka’s Madilog philosophy. Revenue derives from digital advertising, endorsements, crowdfunding, and community-based activities. Flexible and participatory working conditions foster creativity and collaboration but also expose the organization to precarity due to its reliance on platform algorithms and restrictive regulations, including Indonesia's Electronic Information and Transactions Law (UU ITE).